13C stable isotope labeling followed by ultra-high performance liquid chromatography/quadrupole time-of-flight tandem mass spectrometry (UHPLC/Q-TOF MS) was applied to identify the metabolites of honokiol in rat small intestines. Issue 6 (21st March 2015) - Ye, Na; Tang, Minghai; Ye, Haoyu; Wang, Chunyan; Wang, Chunyu; Yang, Qiunan; Wan, Li; Chen, Lijuan
<x xml:space="preserve">Abstract</x> Honokiol, as a pharmacological active small-molecule, has received significant attention for its strong pharmacological effects without remarkable toxicity.